TAMAN BUDAYA DI MANGGA BESAR, JAKARTA BARAT - Syarifa Andari; Rudy Trisno (Jurusan Arsitektur dan Perencanaan, 2020)
Indonesia has many kinds of ethnicities and cultures. Unfortunately, nowadays news about intolerance is often heard in Indonesia. diversity of ethnicities could cause incompatibilities. Each ethnic have their habits and lifestyle. In consequence, this project is made to provide education to all kinds of communities. The form of education is a cultural park, that adopts themes of the Betawi and the Chinese culture because both cultures have many resemblances. This cultural park at the same time can be used as a third place for the local citizens. The third place serves as an intermediary between first places (such as houses, apartments, hotels, home) and second places (such as offices, stores, working space). The third place is flexible, it could be used as a place to relax or even having work meetings with co-workers. This Cultural Park has a traditional concept, with the form that blends in with its site region. As for the methods; Site project analysis; Determining building program; Positive energy method application; Symbiosis method application; Form follows function method application; Luo shu method application; Final project result. In conclusion, Mangga Besar Cultural Park has a goal to educate local citizens about the Betawi and Chinese culture. Mangga Besar Cultural park also applies the symbiosis and form follows function concept and luo shu. In conclusion, Mangga Besar Cultural Park has a goal to provide education to citizens about the Betawi and Chinese culture. This project applies some concepts, such as symbiosis in architecture, form follows function, and luo shu. Keywords: Culture; Ethnicities; Local Citizen; Park; Third PlaceAbstrak Indonesia memiliki berbagai macam suku dan budaya. Namun, belakangan ini sering terdengar masalah mengenai intoleransi di Indonesia. Keberagaman etnis dapat menimbulkan ketidak cocokan dalam bermasyarakat. Masing-masing etnis memiliki kebiasaan dan gaya hidup mereka sendiri. Oleh karena itu, proyek ini dibuat dengan maksud untuk meminimalisir masalah tersebut, dengan memberi edukasi kepada masyarakat dari semua kalangan. Edukasi tersebut berbentuk taman budaya di Jakarta, yang memiliki tema bangunan budaya betawi dan budaya tionghoa yang digabungkan, dikarenakan kedua budaya tersebut saling berselingan. Taman budaya disini juga sekaligus dapat dijadikan sebagai third place bagi masyarakat sekitar. Third Place disini berfungsi sebagai perantara antara first place (rumah, hotel, apartemen, tempat tinggal) dan second place (kantor, pertokoan, tempat kerja). Third place disini memiliki fungsi fleksibel, dapat digunakan untuk bersantai hingga membahas pekerjaan bersama rekan kerja. Taman budaya berkonteks arsitektur tradisional, dengan bentuk yang sesuai dan membaur dengan bangunan sekitarnya. Metode perancangan; Pemahaman Kawasan Jakarta Barat; Pemahaman Mengenai Tapak Perancangan; Penetapan Program Bangunan; Penggunaan Metode Energi Positif; Penggunaan Metode Simbiosis; Penggunaan Metode Form follows function; Penggunaan Metode Luo Shu; Hasil Akhir Perancangan. Kesimpulan dari hasil perancangan adalah Taman Budaya di Mangga Besar memiliki tujuan untuk memberikan edukasi kepada masyarakat mengenai budaya Betawi dan Tionghoa. Proyek ini menerapkan beberapa konsep, seperti simbiosis dalam arsitektur, form follows function dan luo shu.